Role of Bilingualism and Biculturalism as Assets in Positive Psychology: Conceptual Dynamic GEAR Model - Chen, Xinjie; Padilla, Amado M. (Frontiers in Psychology, 2019)
Are bilingualism and/or biculturalism good for a person’s positive well being? A growing number of studies have shown different positive outcomes of being exposed to two cultures or speaking two languages respectively, but the benefits of being both bilingual and bicultural have rarely been investigated theoretically or empirically. The purpose of this paper is to summarize the main beneficial outcomes of bilingualism and biculturalism, and to integrate these benefits into a new conceptual framework： Positive Bilingualism and Biculturalism GEAR model. The GEAR model suggests that the beneficial outcomes of bilingualism and biculturalism can be systematically classified into four positive dimensions (psychological Growth; cognitive Exploration; linguistic Awareness; social Reinforcement), in which there are dynamic interactions among these four dimensions. The hypothetical GEAR model provides an intricate theoretical approach to understand the potential benefits to an individual of experiencing more than one language and one culture in their life. The proposed model in this research offers a systematic framework for conducting future research to examine whether bilingualisms and biculturalism accrue benefits to the individual.